(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
Quality evaluation of biscuits produced from wheat flour using peanut butter as a fat substitute was studied. Five samples were produced using 100% wheat flour (BBZ: 100% butter; RMD: 10% butter and 90% peanut butter; OKW: 20% butter and 80% peanut butter; BFB: 30% butter and 70% peanut butter; FMB: 40% butter and 60% peanut butter) and were subjected to different analyses: mineral, proximate, and vitamin composition, as well as sensory evaluation. The data obtained were statistically analyzed using ANOVA and mean separated by the Duncan Multiple Range Test (p<0.05). The moisture, protein, fat, fiber, ash, and carbohydrate ranged from 7.22 - 9.35%, 3.95 - 4.25%, 18.35 - 26.98%, 0.39 - 1.23%, 1.85 - 2.40% and 56.65 - 66.40% respectively. The samples contain significant (p<0.05) amounts of potassium (27.50-45.00 mg/100g), calcium (202.50-237.50 mg/100g), magnesium (47.50-67.75 mg/100g), iron (7.85-9.25 mg/100g), phosphorus (160.00-195.00 mg/100g), and sodium (262.50-287.50 mg/100g) content. The addition of peanut butter had a significant effect on the mineral content of the biscuits due to the presence of the peanut. The samples contained ascorbic acid (4.80-5.30 mg/100g), vitamin B1 (0.09-0.15 (mg/100g), Vitamin B2 (0.19 - 0.22 mg/100g) and Vitamin B3 (1.73 - 1.83mg/100g). The value of sensory scores for taste, colour, appearance, texture, and overall acceptability ranged from 7.50 - 9.10, 5.70 - 7.10, 7.90 - 8.90, 8.10 - 8.80 and 7.60-8.00 respectively. There was a significant (p<0.05) difference among samples in the sensory panelist ratings of taste, colour, appearance, texture, and overall acceptability.